1, 4-Additions of tricyclic 1, 4-diphosphinines – a novel system to study σ-bond activation and π–π dispersion interactions. Issue 10 (12th January 2018) - Koner, Abhishek; Kelemen, Zsolt; Schnakenburg, Gregor; Nyulászi, László; Streubel, Rainer
Abstract : The reactivity of the aromatic π-system in 1, 4-diphosphinineI was explored towards [4+2]-cycloaddition reactions along with activation of organo dichalcogenides under thermal conditions. Abstract : The dienic nature of the aromatic π-system in 1, 4-diphosphinines remains largely unexplored to this day due to a lack of facile and efficient synthetic protocols. Recently reported stable, tricyclic 1, 4-diphosphinines were used to explore the thermal reactivity of the π-system towards an array of dienophiles in [4π+2π]- and, for the first time, in [4π+2σ]-type cycloaddition reactions.